ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITRA TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PT MYFAST SOLUTIONS) - Faisal, F; Nugroho, R. Eddy (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research was intended to analyze the influence of service quality, price and image towards customer satisfaction and its impact on customer loyalty at PT. My fast Solutions. The company offers sales and services, especially in the management of health funds including insurance products. The design of this research is a causal research design that is research conducted to identify causal relationships between variables. Primary data was obtained through surveys with questionnaires distributed to customers or prospective customers of PT. My Fast Solutions. Sampling method used in this research is saturated sampling method, as many as 50 respondents selected to this sample. This research uses descriptive method with quantitative approach. The test statistic used is t statistic or t test, if obtained p-value ≤ 0.05 (alpha 5%) means significant. Analytical aids using SmartPLS 3.0. The results showed that the quality of service and image significant influences on customer satisfaction and also loyalty. However, price perception did not have a significant effect on customer satisfaction and customer loyalty. While customer satisfaction had a significant influence on customer loyalty. This research can be a recommendation for the company for managerial policy decision at PT. My fast Solutions especiall to improve the quality of services and image in order to maintain its customer loyalty